2021
DOI: 10.1002/1878-0261.13141
|View full text |Cite
|
Sign up to set email alerts
|

The TRAR gene classifier to predict response to neoadjuvant therapy in HER2‐positive and ER‐positive breast cancer patients: an explorative analysis from the NeoSphere trial

Abstract: As most erb‐b2 receptor tyrosine kinase 2 (HER2)‐positive breast cancer (BC) patients currently receive dual HER2‐targeting added to neoadjuvant chemotherapy, improved methods for identifying individual response, and assisting postsurgical salvage therapy, are needed. Herein, we evaluated the 41‐gene classifier trastuzumab advantage risk model (TRAR) as a predictive marker for patients enrolled in the NeoSphere trial. TRAR scores were computed from RNA of 350 pre‐ and 166 post‐treatment tumor specimens. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(50 reference statements)
1
1
0
Order By: Relevance
“…Even if based on a small sample cohort, our data provided evidence of the predictive value of HER2 mRNA in both ER-positive and ER-negative subgroups of adjuvant trastuzumab-treated patients, supporting the possibility that HER2 predictive value could be relevant mainly in patients with expression of both ER and HER2, especially in an adjuvant treatment setting. This hypothesis is supported by our data on the predictive value of TRAR, in which HER2 and ESR1 are core genes only in ER-positive tumors of the NeoSphere trial [ 33 ], and the data of the Gepar IV trial, which showed that pCR rate continuously rose with increases in HER2 mRNA levels only in ER-positive tumors [ 12 ].…”
Section: Discussionsupporting
confidence: 54%
“…Even if based on a small sample cohort, our data provided evidence of the predictive value of HER2 mRNA in both ER-positive and ER-negative subgroups of adjuvant trastuzumab-treated patients, supporting the possibility that HER2 predictive value could be relevant mainly in patients with expression of both ER and HER2, especially in an adjuvant treatment setting. This hypothesis is supported by our data on the predictive value of TRAR, in which HER2 and ESR1 are core genes only in ER-positive tumors of the NeoSphere trial [ 33 ], and the data of the Gepar IV trial, which showed that pCR rate continuously rose with increases in HER2 mRNA levels only in ER-positive tumors [ 12 ].…”
Section: Discussionsupporting
confidence: 54%
“…[270][271][272][273] ). Furthermore, gene expressionbased tools for prognostic and predictive purposes are also under evaluation in HER2 + breast cancer, although none of these has yet reached mainstream use 274,275 .…”
Section: Her2 Diagnosticsmentioning
confidence: 99%